Correlation between time-resolved and integral mesurements of the soft X-ray emission in a plasma focus operated in argon - Eliseev, S.P.; Nikulin, V.Ya.; Silin, P.V. (Вопросы атомной науки и техники, 2008)
The results of experiments received on the plasma focus (PF) device with energy stored equal 1.5-5 kJ are represented in this paper. Discharge integral photos were obtained with the help of the soft x-ray pinhole camera with four 250 μm apertures. Simultaneously the short X-ray pulse recording system was fulfilled by the fast semiconductor detectors SPPD11-04 hided 50 μm Be filters with exposure time about 1.5 ns. The soft X-ray measurements were fulfilled in the voltage range U=8-14 kV and argon pressure 1.3-3.2 Torr. Under some conditions transition from hot spots regime to column type was observed by the 50 μm pinhole camera. With help of the 20 μm pinhole camera was estimated size of the hot spots about 13-25 μm radiated quanta with energy ≥ 1.8 keV.